The Effect of Fast Food Digital Marketing on Purchase Intention Through Brand Image and Consumer Satisfaction (Study on KFC Palopo's Teen Consumers) - Windarsari, Wiwin Riski; Sudarmiatin, Sudarmiatin; Siswanto, Ely (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2022)
The Theory of Planned Behavior (TPB) by including three additional constructs namely digital marketing, brand image, and consumer satisfaction to predict adolescent purchase intention for fast food products. This study uses an explanatory quantitative approach. The sampling technique used purposive sampling totaling 200 respondents. Data analysis using Partial Least Square (PLS) method. The results of the study show that 1) digital marketing has a positive and significant direct effect on brand image. 2) digital marketing has a positive and significant direct effect on consumer satisfaction. 3) brand image has a positive and significant direct effect on purchase intention. 4) consumer satisfaction has a positive and significant direct effect on purchase intention. 5) digital marketing has a positive and significant direct effect on purchase intention. 6) brand image has a direct effect on consumer satisfaction. 7) digital marketing has a positive and significant direct effect on purchase intention through brand image. 8) digital marketing has a positive and significant direct effect on purchase intention through consumer satisfaction. 9) brand image has a positive and significant direct effect on purchase intention through consumer satisfaction. 10) digital marketing has a positive and significant direct effect on consumer satisfaction through brand image. Based on the results of the study, the researchers gave suggestions, namely adding social media campaigns and providing special product packages for teenagers